“ABED TANGI” As a Solution for Time Inaccuracy in Returning Medical Record at X Hospital - Ika Rahayu Susanti; Andriyani Hamzah; Siti Asiyah Anggraeni; Kurnia Widyaningrum (Universitas Muhammadiyah Yogyakarta, 2018)
This study aims to determine the root of problem and alternative solutions of inaccuracy return medical record inpatient files. The research was conducted through qualitative descriptive approach in RSUD Blambangan from September until October 2017. Data was collected by document review, field observation and unstructured interview with Head of Services, Head of Nursing Services, 1 doctor, 2 head of ward, Head of Medical Record Installation, Head of Nutrition Installation and Head of Pharmacy Installation. Root of problem was analyzed with fishbone diagram, focus group discussion (FGD) method and urgency, seriousness, growth (USG) method. Priority determination solution is carried out using filter analysis method with CARL (Capability Accessibility Readiness Leverage). The results show that factor inaccuracy return inpatient medical records file because are incomplete of medical record file, absence of standard operating procedure and unavailability of monitoring and evaluation, and the increasing number of medical record form according to hospital quality standard. The root problem is not optimally main task and function of professional care giver when filling medical record. Alternative proposed solutions is socialization to professional care giver, revised standard of operational procedure, and monitoring evaluation of the completeness and timeliness of medical record file returns with innovation